MEKANISME PERTANGGUNGJAWABAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (STUDI KASUS D.I. YOGYAKARTA) - Mailinda Eka Yuniza; Adrianto Dwi Nugroho (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2013)
The Regional Budget Implementation Accountability (PPAPBD) mechanism is a part of the regional financing management process applicable subsequent to the formulation of draft APBD, approval ofthe draft APBD by the Regional House of Representatives, validation by the Central Government,enactment of draft APBD to be APBD, and implementation of APBD. In a normative manner, the PPAPBDmechanism is a series of supervisory procedures performed by budget-supervisory institutions, amongothers include the Board of Financial Audit (BPK), the Ministry for Domestic Affairs, and the RegionalHouse of Representatives. Within the field of administrative law, the PPAPBD mechanism is a form of administrative supervision performed in order to establish good governance in accordance with the General Principles of Good Governance (AUPB). Mekanisme Pertanggungjawaban Pelaksanaan APBD (PPAPBD) merupakan bagian dari proses pengelolaan keuangan daerah setelah proses penyusunan Rancangan APBD, persetujuan RAPBD oleh DPRD, pengesahan APBD oleh Pemerintah Pusat, penetapan menjadi APBD, dan pelaksanaanAPBD selesai dilakukan. Secara normatif, mekanisme PPAPBD merupakan suatu rangkaian prosedurpengawasan yang dilakukan oleh instansi-instansi yang memiliki fungsi pengawasan anggaran, antaralain Badan Pemeriksa Keuangan (BPK), Kementerian Dalam Negeri, dan Dewan Perwakilan RakyatDaerah (DPRD). Dalam konteks hukum administrasi negara, mekanisme PPAPBD merupakan bentukpengawasan demi terwujudnya pemerintahan yang baik sesuai dengan antara lain Asas-Asas UmumPemerintahan yang Baik (AUPB).